Implementasi Knowledge Management dalam Sistem Supply Chain Agroindustri - Evi Savitri Iriani (Agroindustrial Technology, University of Trunojoyo Madura, 2010)
Knowledge Management (KM) and supply chain is a new approach used by many companies to create value, increase organizational effectivity and productivity, and competitiveness. However, this concept is still rarely used in agroindustry. The integration of KM and supply chain is very important. A supply chain which applies knowledge managemen system in all the chains will get the final value larger than the total values of all chains, and thus improve competitiveness f the product. The application of KM is initiated by collecting information from supply chain system which were then analysed and shared with all of the components of all chains to support decision making process. A key of success in the implementation of KM is knowledge sharing among components within the system. Another important factor is leadership to support the implementation of KM and colaboration with other parties